Etiological agents of suppurative corneal ulcer: Study of 56 cases (Bangladesh Journal of Medical Microbiology, 2010)
This study was carried out to isolate and identify the etiological agents causing suppurative corneal ulcers and to perform the antimicrobial susceptibility testing of the bacterial isolates. Samples (corneal swabs and scrapings) were collected aseptically from 56 suppurative corneal ulcer patients attending Rajshahi Medical College Hospital (RMCH). Isolation and identification of the microbial agents and antimicrobial susceptibility testing were done in the Microbiology laboratory of Rajshahi Medical College. Culture yielded growth in a total of 47(83.93%) cases out of 56 patients with pure fungal growth, pure bacterial growth and mixed microbial growth (both bacteria and fungi) in 24(42.86%), 14(25.0%), and 09(16.07%) cases respectively. Among the fungal isolates, Aspergillus fumigatus was the leading agent detected in 10(30.30%) cases followed by Fusarium spp, Mucor spp, Aspergillus flavus, Aspergillus niger, Rhizopus spp, Unidentified branching fungus and Alternaria spp. found in 08(24.24%), 04(12.12%), 03(9.09%), 02(6.06%), 02(6.06%), 03(9.09%) and 01(3.03%) cases respectively. Staphylococcus aureus was the leading bacterial pathogen found in 10(43.47%) cases followed by Pseudomonas spp., H. influenzae, Staph. epidermidis, Strept. pneumoniae and E. coli detected in 05(21.73%), 03(13.04%), 02(8.69%), 02(8.69%) and 01(4.35%) cases respectively. Lomefloxacin, Tobramycin and Gentamicin were found to be better efficacious drugs against most of the bacterial pathogens noted in in-vitro susceptibility testing. This limited study has revealed and reinforced that suppurative corneal ulcers are caused by both bacterial and fungal agents with fungal preponderance in this geographical area and Lomefloxacin, Tobramycin and Gentamicin are better choice of antibiotics to treat bacterial suppurative corneal ulcers patients.Bangladesh J Med Microbiol 2010; 03 (02): 33-36